KAHOOT AS THE MEDIA PLATFORM FOR LEARN ENGLISH - Fathan, Umar Said Abdullah; Syafii, Ahmad (Universitas Nusantara PGRI Kediri, 2018)
Nowadays, we lived in virtue era that everything will use glass or screen. Every student also will follow the era. Most of the students are holding the gadget wherever they go. Nairn in Joanna Canny (2013) states that children spend twice as much time in front of a screen (like televisions, computers, mobile phones, iPods, iPads, etc.). Even in the classroom they looking for their task and open their gadget. In this case, English Language Teacher should follow the era. Caused the students always hold the gadget, the teachers should provide the media that related to the gadget. To solve this case kahoot comes and bring new innovation. This media really awesome with nice features which are colorful, shape, sound, and others feature that include in. Through this media, the teacher will manage the students with a fun learning like kahoots’ tagline “make learning awesome”. It will give the students attractive in learning English. Keywords: Media platform, Kahoot, English Language Teacher